PERENCANAAN LANSKAP RIPARIAN SUNGAI MARTAPURA UNTUK MENINGKATKAN KUALITAS LINGKUNGAN ALAMI KOTA BANJARMASIN - Siti Nurisjah; Lisa Anisa (http://arl.faperta.ipb.ac.id/, 2011)
Rivers are part of natural resources which increasing the city’s natural environment quality. So as, Banjarmasin City which has ±107 rivers and known as ”The Thousand Rivers City”. The research objective was to plan riparian landscapes of Martapura River to increase the Banjarmasin City’s natural environment quality. The river was divided into seven segments to classified its natural character (sinuosity) and natural environment quality (open spaces and land cover). Qualitative and spasial methods were carried out to analyze data and to plan the riverscape. The research found three types of environmental zones along the river. Basedon three environmental zones, the Martapura riparian was planned spasially to be urban forest, vegetated city park and city park types. To increase natural and local natural beauty, it is proposed to plant the endemic and local types of vegetation